PENGARUH LITERASI KEUANGAN, UANG SAKU, DAN GAYA HIDUP TERHADAP MINAT MENABUNG MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Razi, Safwan; Syahrudin, Husni; Budiman, Jumardi (Jurnal Edukasi Ekonomi, 2023)
This study aims to determine the effect of financial literacy, pocket money, and lifestyle on the interest in saving economic education students FKIP Tanjungpura University Pontianak. The sampel in this study amounted to 103 of the population of 157 students. This research method uses quantitative research with path analysis. The data collection technique used a questionnaire which was distributed to economic education students from class 2020 to 2022. The result of this study found that financial literacy has an effect on interest in saving whit a significant value of 0.628, pocket money does not have a significant effect on interest in saving whit a significant value of 0.336 and a path coefficient value of 0.115, and lifestyle does not have a significant effect on interest in saving economic education students FKIP Untan with a significant value of 0.387 and a path coefficient value of -0.098. Financial literacy through lifestyle affects the interest in saving of economic education students of FKIP Untan with a path coefficient value of 0.659. My money through lifestyl affects the interest in saving of economic education students of FKIP Untan with a path coefficient value of 0.160.